Seismic Lateral Load Pattern for Infill Low-Rise Buildings with a Stiffness-Related Soft First Story. Issue 7 (July 2015) - Chen, Shi-Shuenn; Shi, Jun-Yang
The observation of post-earthquakes damages on buildings has shown that the presence of nonstructural infill walls may significantly affect the seismic performance of buildings. This study aims to develop an equivalent lateral load pattern for infill low-rise buildings with a soft first story subjected to seismic excitations. The proposed load pattern features using a simple way to consider stiffness irregularities induced by infill walls. The distribution of story shear evaluated from static analysis using the proposed lateral load pattern is found to be close to the result analyzed from response spectrum analysis. Moreover, the dynamic response of the infill building is dominated by the first mode when the building has a stiffness-related soft first story. The proposed lateral load pattern may be used in seismic design of low-rise buildings to effectively consider the infill walls for improving seismic safety.